Analyzing diversification possibilities on specialized tobacco farms in Argentina using a bio-economic farm model - Chavez Clemente, Maria Daniela (2014)
Tobacco (Nicotiana tabacum L.) is the non-food crop with the largest acreage in the world. Tobacco is criticized because it causes health problems to its consumers and because production causes environmental damage such as soil degradation, deforestation and water pollution. Diversification has been indicated as the strategy for a sustainable economic development for farmers. In the specific case of Valle de Lerma, many years of continuous tobacco mono-cropping, excessive ploughing and poor irrigation control have caused soil degradation of the land used for tobacco. Tobacco farming in Salta also entails a production and a price risk which is increasing because of uncertainty surrounding governmental subsidies. The objective of this article is to assess the impact of diversification on expected farm income, income risk and soil organic matter (as an indicator of soil degradation) on specialized tobacco farms. To reach this objective, a quadratic programming model of a typical specialized tobacco farm is developed. Soil organic matter is included in the model by means of the concept of the carbon balance. The carbon balance is the difference between carbon supply and carbon decline in a year. Two different situations with respect to soil degradation are evaluated using the model. The current situation includes no restriction on carbon balance while the desired situation includes the restriction that the carbon balance cannot be negative. So farmers’ choices are valuated with and without carbon balance constraints. The model results for the current situation show that, no matter which risk attitude is used, the maximum area of land given irrigation possibilities is devoted to tobacco, while the rest of the land is assigned to the non-irrigated crop soybean. The carbon balance is negative and soil continues to degrade. In the desired situation, tobacco and soybean are partly replaced by bull beef production (including the production of alfalfa and maize for silage) to fulfill the requirement of a no negative carbon balance. As the risk aversion coefficient in this situation increases, the low risk crop chickpea enters the solution and bull beef decreases. The requirement of no further soil degradation comes at a high cost since gross margin of the farm is decreased by some 35% compared to the current situation. Finally, the model is used to explore the effects of an abolishment of governmental subsidies on tobacco. In this situation the production plan consists of soybean, bull beef and tobacco in such a proportion that the carbon balance is positive. Income effects of an abolishment of governmental subsidies on tobacco would be large as the gross margin of the farm decreases by some 60%.